2021
DOI: 10.1002/cjce.23936
|View full text |Cite
|
Sign up to set email alerts
|

CO2 mobility control by small molecule thickeners during secondary and tertiary enhanced oil recovery

Abstract: Recently, polymer thickeners have been considered for CO2 mobility control during enhanced oil recovery (EOR) processes. Despite that, the requirement of co‐solvents is a controversial challenge for the solution of high‐molecular weight thickeners in gases. This study is focused on small molecule thickeners for carbon dioxide EOR without adding co‐solvents. Polydimethylsiloxane (PDMS) was used as a CO2‐philic thickener in different low molecular weights. Cloud‐point pressure, relative viscosity, and interfacia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…For example an "HTHP falling ball viscometer" (no details provided) was used to detect a 3.5-fold increase in viscosity at 25 °C and 3,400 psi using 2 wt % PDMS, and a 3.7-fold increase at 4 wt %. 37 We urge caution when considering the results of Gandomkar and co-workers because their thickening results for low molecular weight PDMS are much more dramatic than those observed by our team. Further, the Gandomkar thickening results are comparable to the results reported by Chevron even though Chevron employed significantly higher molecular weight PDMS.…”
Section: Introduction To the Need For Thickened Co 2 During Enhanced ...mentioning
confidence: 63%
See 1 more Smart Citation
“…For example an "HTHP falling ball viscometer" (no details provided) was used to detect a 3.5-fold increase in viscosity at 25 °C and 3,400 psi using 2 wt % PDMS, and a 3.7-fold increase at 4 wt %. 37 We urge caution when considering the results of Gandomkar and co-workers because their thickening results for low molecular weight PDMS are much more dramatic than those observed by our team. Further, the Gandomkar thickening results are comparable to the results reported by Chevron even though Chevron employed significantly higher molecular weight PDMS.…”
Section: Introduction To the Need For Thickened Co 2 During Enhanced ...mentioning
confidence: 63%
“…It has been recently reported by Gandomkar and co-workers that PDMS oligomers (4,800 < MW < 10,000) are indeed remarkable CO 2 thickeners. For example an “HTHP falling ball viscometer” (no details provided) was used to detect a 3.5-fold increase in viscosity at 25 °C and 3,400 psi using 2 wt % PDMS, and a 3.7-fold increase at 4 wt % . We urge caution when considering the results of Gandomkar and co-workers because their thickening results for low molecular weight PDMS are much more dramatic than those observed by our team.…”
Section: Introduction To the Need For Thickened Co2 During Enhanced O...mentioning
confidence: 89%
“…These thickeners are designed to increase the viscosity of injected CO 2 , addressing issues like viscous fingering and early breakthrough. 45 This study delves into a novel approach for enhancing CO 2based EOR by untangling the intricate interplay between brine salinity, MB stability, and foam generation. It investigates how specific surfactant concentrations, optimized brine is-to-oil ratio, and moderate gas flow rates can be fine-tuned to improve the stability and longevity (half-life) of CO 2 MBs and the resulting foam.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecule thickeners play a crucial role in CO 2 mobility control during secondary and tertiary EOR processes. These thickeners are designed to increase the viscosity of injected CO 2 , addressing issues like viscous fingering and early breakthrough …”
Section: Introductionmentioning
confidence: 99%
“…The implementation of CO 2 – EOR can be done under several schemes, including the injection of miscible/immiscible CO 2 , water alternating CO 2 gas injection (WAG CO 2 ), polymer alternating gas CO 2 (PAG), simultaneous water CO 2 gas injection, foam assisted CO 2 , low salinity water–surfactant–CO 2 , and hybrid schemes with surfactant polymer (SP). Most CO 2 – EOR processes are commonly confronted to satisfy two objectives consisting of maximizing ORF and minimizing the production of CO 2 (this latter means the increase in the storage performance). However, it is worth mentioning that many published studies and experimental tests demonstrated the superiority of the miscible type (single–phase flow) of CO 2 – EOR processes in reaching higher ORF compared to the immiscible type (two–phase flow). , The suitable design of a CO 2 – EOR process depends greatly on the so-called minimum miscibility pressure (MMP) since this parameter allows the determination of the injection type, i.e., miscible or immiscible. MMP represents the cutoff pressure at reservoir temperature (T R ) above which miscibility between the reservoir fluid and the injected gas occurs after multiple contacts. …”
Section: Introductionmentioning
confidence: 99%